Women for water sharing - Moudud, Hasna Jasimuddin, 1946- (Dhaka : Academic Publishers, 1995)
Sharing of water of Ganges River by Bangladesh and India at Farakka Dam, and the resulting adverse effects on Bangladesh; contributed articles.
Includes bibliographical references.
Keywords: Water resources development -- Ganges River Region (India and Bangladesh) -- International cooperation; Environmental policy -- Bangladesh; Ganges river (India and Bangladesh) -- Water rights